2022
DOI: 10.3390/ijms231810978
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic Acid Attenuates Inflammation Induced by Salmonella via Upregulating LncRNA TVX1 in Microglia

Abstract: Salmonella typhimurium (S.T) induces damage to the central nervous system; however, the role of Asiatic acid (AA) in this is still unknown. Microglia play a role as macrophages to recognize the invaded pathogenic microbes in the brain. The aim of this study was to investigate the protective effect and mechanism of AA on the central nervous system through an in vitro model of S.T infection in microglia. We pre-treated microglia with AA before S.T infection and explored the anti-infection mechanism of AA by sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Lai et al found that AA inhibits malignant processes such as human prostate cancer cell proliferation and migration by mediating the MZF-1/Elk-1/Snail signaling axis, providing new potential targets for treating human prostate cancer [ 33 ]. By reducing new blood vessel formation, AA can inhibit tumor blood supply, reducing the likelihood of its growth and spread [ 34 ]. In this study, AA concentration-dependently inhibited CC cell proliferation, migration, and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Lai et al found that AA inhibits malignant processes such as human prostate cancer cell proliferation and migration by mediating the MZF-1/Elk-1/Snail signaling axis, providing new potential targets for treating human prostate cancer [ 33 ]. By reducing new blood vessel formation, AA can inhibit tumor blood supply, reducing the likelihood of its growth and spread [ 34 ]. In this study, AA concentration-dependently inhibited CC cell proliferation, migration, and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Hosts deficient in IFNG-AS1 exhibit increased vulnerability to fatal infection with Salmonella enteritidis , highlighting the crucial role of IFNG-AS1 in the host defense against Salmonella infections [ 67 ]. In addition to its gastrointestinal impact, S. typhimurium can also affect the central nervous system, with studies, like those by Zou et al, indicating that lncRNA TVX1 can mitigate S. typhimurium -induced microglial inflammation [ 68 ].…”
Section: Lncrnas In Bacterial Zoonosesmentioning
confidence: 99%
“…It is evident from the above data analyses that there are many up-regulated genes in both monocytes and macrophages after NLRP3 inflammasome activation; some of which are shared among different conditions (Figure 3A; Supplementary Tables S3 and S4). To date, only a few lncRNAs have been studied in relation to the NLRP3 inflammasome activation in inflammatory cells, especially in macrophages [24][25][26][27][28][29][30][31][32][33][34][35]. To address this point, we selected both protein-coding and lncRNA genes whose expressions were up-regulated in the above-analyzed RNA-seq data (Supplementary Table S5).…”
Section: Expression and Functional Analysis Of Inflammasome-regulated...mentioning
confidence: 99%